A Comparison of two Decision Support Systems Designed for a Dispatching Problem - Cutrona, C.S.; Pratsch, C.; Valcarengh, C.; Welter, A.; de Macedos Guimaraes, L.B.; Guerlain, S. (2006 IEEE Systems and Information Engineering Design Symposium, 2006)
This paper compares two decision support system designs to aid in the daily dispatching of trucks delivering oil from Tenoas, an oil distributor, to hundreds of locations in the southernmost state of Brazil. On site research and interviews were conducted in order to determine the needs of the system and the greater implications for drivers, managers, and dispatchers. This analysis led to the functional requirements which, at the highest level, are to create a fair yet understandable and editable procedure for determining the daily dispatching of truckers. Both designs display customer orders and available trucks, and aid the user to manually or automatically assign drivers to routes by displaying relevant information needed for the decision making process. One uses a matrix layout and the other a map layout. The two designs are compared in their workflow and the likely impact they would have on the workers. The final system, if implemented, will have implications for many of the workers at Tenoas, including the programmers, who can create truck/location assignments more efficiently, the truck drivers who do not have to wait as long and are subjects of a fairer system, and the managers who are adopting a technology that is more socially responsible